African Emancipation and Its Forms of Politic Organization - (:unkn) unknown (My University, 2022)
This paper thematizes some questions about African emancipation, and its emerging forms of political organization for liberation and the acquisition of self-government. The cases of South Africa and Ghana are mentioned with some emphasis. The processes of decolonization are an important issue for understanding 20th century politics. Related to this is the emergence of movements and parties that mark the spread of socialism in the black continent, and the complex relations of each emancipated country with the colonial powers, relations crossed by economic, political, racial and tribal interests. Likewise, reference is made to the peculiar importance of leaders and incipient political elites in the processes of emancipation and self-government.
Keywords: African Research